2005
DOI: 10.1063/1.1988973
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of Si1−xMnx alloys on Si(100)

Abstract: Si 1 − x Mn x alloy films of 50 nm thickness with 0.005⩽x⩽0.035 were grown by low-temperature molecular-beam epitaxy onto Si(100) substrates held at temperatures T in the range of 150°C⩽T⩽350°C. All films exhibit surface roughness with ∼20-nm-lateral and ∼1-nm-vertical length scales. This roughness is random for films with small x grown at the lower end of the temperature range. Films with larger x grown at higher T exhibit roughness organized into ⟨110⟩-oriented cluster arrays centered on shallow surface depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…17,18 No essential manifestations of HT FM caused by these nanocolumns were revealed in Refs. 17 and 18.…”
Section: Structure Measurementsmentioning
confidence: 99%
“…17,18 No essential manifestations of HT FM caused by these nanocolumns were revealed in Refs. 17 and 18.…”
Section: Structure Measurementsmentioning
confidence: 99%
“…In the ideal bulk MnSi 1.7 27 Si 47 revealed that these phases are half-metallic, with full spin polarization of the carriers (holes) at the Fermi level. On the contrary, the ideally stoichiometric and unstressed Mn 4 Si 7 silicide is shown to be a semiconductor, with indirect band gap, although small nonstoichiometry or stress lead to the closure of the gap, transforming the material into a metal.…”
Section: Setup Of the Problemmentioning
confidence: 99%
“…Moreover, there is experimental evidence for the formation of vertical Mn-enriched nanopipes in Si 1−x Mn x alloys grown on a Si(100) substrate. 27 Also the inspection of the local environment of Mn in the Mn δ-doped Si samples prepared by MBE on Si(001) substrates did not exclude a precipitation. 28 We point out that, in the case of the layer, the averaging procedure to determine ϕ(r) consists in integrating over the Cartesian coordinates parallel to the layer (say, y and z).…”
Section: Boundary-induced Fm Ordering In the Precipitatementioning
confidence: 99%
“…Growth of polycrystalline Mn-doped Si with Mn composition more than 0.1 was carried out on Si (001) substrate at T S ¼ 300 C by using gas-source MBE [209]; it was, however, later shown that there is formation of Mn-rich precipitates during MBE growth even at T S ¼ 150 C [210]. Growth of polycrystalline Mn-doped Si with Mn composition more than 0.1 was carried out on Si (001) substrate at T S ¼ 300 C by using gas-source MBE [209]; it was, however, later shown that there is formation of Mn-rich precipitates during MBE growth even at T S ¼ 150 C [210].…”
Section: Iv-based Magnetic Semiconductorsmentioning
confidence: 99%